İnönü üniversitesi dişhekimliği fakültesine başvuran hastalarda taurodontizm görülme prevalansının retrospektif olarak değerlendirmesi - Esma Umar; Numan Dedeoglu; Oguzhan Altun (Cumhuriyet University, 2014)
Objectives: The objective of this study was to determine the prevalence of taurodontism in patients admitting to Dentistry Faculty of Inonu University, and to examine the localization, distribution and the gender differences of taurodontism. Materials and Methods: This retpospective study was carried out using panoramic radiographs of the patients who came to İnönü Univercity Faculty of Dentistry, Departman of Dentomaksillofacial Radiology for dental problems.Results: Among the evaluated of 981 patients, 64 taurodont teeth were found in 31 patients, 8 of them were male (%25.8) and 23 of them were female(%74.2). Ten of cases were hypotaurodont (%15.63), 13 were mesotaurodont (%20.31),  26 were hypertaurodont (%40.62)  and 15 cases were  pyramidal (%23.44). The maxilla was affected more frequently than the mandible, the most common taurodont tooth was the  mandibular 2nd molar.Conclusions: As a result, the prevalence of taurodontism was found to be %3.2. ÖZETAmaç: Bu çalışmanın amacı İnönü Üniversitesi Diş Hekimliği Fakültesine başvuran hastalarda taurodontizm prevalansını belirlemek, lokalizasyonu, dağılımını, cinsiyetler arasındaki farklılığını incelemektir.Gereç ve Yöntem: Bu çalışmada çeşitli dental problemler nedeniyle İnönü Üniversitesi Diş Hekimliği Fakültesi Ağız Diş ve Çene Radyolojisi bölümüne başvuran hastaların dijital panoramik radyografları retrospektif olarak değerlendirildi.Bulgular:  Çalışmaya dahil edilen 981 hastadan 8'i erkek (%25,8), 23'ü kadın (%74,2), toplam 31 hastada 64 taurodont diş bulundu. Bunların 10 tanesi hipotaurodont (%15,63), 13 tanesi mezotaurodont (%20,31), 26 tanesi hipertaurodont (%40,62)   ve 15 tanesi piramidal (%23,44)  olarak belirlendi. Mandibulada maksillaya oranla daha sık görülmüştür. Taurodontizmin en sık rastlandığı diş mandibular 2. molar diştir.Sonuçlar: Taurodont diş prevalansı %3,2 oranında bulundu.